Serangan Ransomware terhadap Infrastruktur Energi di Amerika Serikat Studi Kasus Colonial Pipeline Ransomware Attack - Andrew Bezaliel Tamba (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This thesis analyzes the impact of and the United States’ response to ransomware attacks targeting critical energy infrastructure through a case study of the ransomware attack on Colonial Pipeline in May 2021. The cyberattack, carried out by the DarkSide hacking group, forced the shutdown of the largest fuel pipeline network in the United States, which supplies approximately 45 percent of the fuel consumed along the East Coast. This study employs a qualitative case study methodology and content analysis approach to examine cybersecurity vulnerabilities within energy infrastructure and the strategies adopted by the U.S. government in addressing such threats. The findings indicate that the Colonial Pipeline ransomware attack not only disrupted company operations but also triggered fuel shortages, public panic, and significant economic consequences. Using cybersecurity and national security perspectives, the analysis demonstrates that attacks on critical infrastructure have evolved into strategic threats capable of affecting both economic stability and national security. The United States government responded through stronger public-private sector cooperation, enhanced national cybersecurity policies, and law enforcement measures that successfully recovered part of the ransom payment made to the attackers. This study concludes that the Colonial Pipeline incident marked a significant turning point in U.S. cybersecurity policy and highlighted the urgent need to strengthen cyber resilience across the energy sector in order to address increasingly sophisticated ransomware threats in the future.